Metabolic Profiling of 5xFAD Mice Hippocampal Interstitial Fluid after Cognitive Stimulation: a Pilot Study - Komleva, Yu.K.; Averchuk, A.S.; Chistyakov, D.V.; Vasil’ev, V.G.; Ivlev, V.A.; Zhdankina, V.I.; Kukla, M.V.; Lukyanchuk, A.N.; Potapenko, I.V.; Salmina, A.B. (Biomedical Chemistry: Research and Methods, 2025)
Alzheimer`s disease (AD) is increasingly viewed as a condition associated with disruptions in brain energy metabolism, contributing to synaptic and cognitive impairments. While metabolic disturbances in AD are well characterized under resting conditions, much less is known about the hippocampal response to cognitive stimulation that requires high metabolic flexibility. In this pilot study, using in vivo microdialysis and highresolution NMR spectroscopy, we analyzed the metabolic profile of interstitial fluid in the hippocampus of 5xFAD transgenic mice and control C57BL/6 animals on days 7 and 28 following cognitive training in a conditioned passive avoidance paradigm. Among the metabolites examined, significant differences were found for acetone: in 5xFAD animals on day 28, its concentration was markedly lower compared to controls, indicating a limited ability to maintain ketone metabolism in the delayed post-training period. Other metabolites (acetate, lactate, caprate, isobutyrate, and glycine) did not show significant differences between groups; however, the observed changes may indicate shifts in the utilization of alternative energy substrates. These data suggest reduced hippocampal metabolic plasticity in transgenic animals, particularly in the late phase following cognitive stimulation, which could potentially limit long-term cognitive adaptation. Despite the limitations of this pilot study, the results highlight the potential of an approach combining metabolic profiling in vivo for the early detection of metabolic disturbances and the search for potential biomarkers of neurodegenerative processes in AD.